Pemetaan konformal daerah banyak segi melalui persamaan kamiran terhadap Inti Bergman dan Inti Szego. - Hurmin, Baharudin; Mohamed Murid, Ali Hassan (Department of Mathematics, Faculty of Science, 2004)
A numerical method is described for computing conformal mapping from a simply connected region with corners onto the unit disk. The numerical method is based on the Fredholm integral equations for Bergman and Szego kernels. The numerical method for solving the integral equations is based on the Nystrom method with trapezoidal rule.